2007
DOI: 10.1002/ajmg.a.31860
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice site mutation in EYA4 causes DFNA10 hearing loss

Abstract: Nonsyndromic autosomal dominant sensorineural hearing loss (SNHL) at the DFNA10 locus was described in two families in 2001. Causative mutations that affect the EyaHR domain of the 'Eyes absent 4' (EYA4) protein were identified. We report on the clinical and genetic analyses of an Australian family with nonsyndromic SNHL. Screening of the EYA4 gene showed the novel polypyrimidine tract variation ca. 1,282-12T > A that introduces a new 3' splice acceptor site. This is the first report of a point mutation in EYA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…One locus at 6q26 -q27 identified by linkage analysis in a consanguineous family is associated with autosomal recessive congenital sensorineural deafness, whereas the other region at 6q23.2 harbors the EYA4 gene implicated in later onset of autosomal dominant hearing loss. 23,24 Our data suggest that microcephaly, ACC and hearing loss seen in interstitial or terminal deletions involving 6q25 may map to a 3.52-Mb region at 6q25.2 -q25.3. This region harbors 12 protein-coding genes ( Figure 5); among them, the ones that may be pertinent to the clinical phenotype are TIAM2, NOX3 and SYNJ2.…”
Section: Nervous Systemmentioning
confidence: 74%
“…One locus at 6q26 -q27 identified by linkage analysis in a consanguineous family is associated with autosomal recessive congenital sensorineural deafness, whereas the other region at 6q23.2 harbors the EYA4 gene implicated in later onset of autosomal dominant hearing loss. 23,24 Our data suggest that microcephaly, ACC and hearing loss seen in interstitial or terminal deletions involving 6q25 may map to a 3.52-Mb region at 6q25.2 -q25.3. This region harbors 12 protein-coding genes ( Figure 5); among them, the ones that may be pertinent to the clinical phenotype are TIAM2, NOX3 and SYNJ2.…”
Section: Nervous Systemmentioning
confidence: 74%
“…(HA-E193) were commercially obtained, the latter corresponding to the human mutation identified and first described by Schoenberger et al 1 It encodes the 193 N-terminal amino acids of wild-type E193, followed by 29 new aa and a termination signal. Both constructs were amplified by PCR, digested and separately cloned into a mammalian expression vector enclosing the mouse α-MHC promoter.…”
Section: Supplementary Methodsmentioning
confidence: 99%
“…The E193 construct corresponds to the human E193 mutant identified and described by Schoenberger et al 1 Adenovirus encoding shRNA against murine Eya4 (pAd-shRNA_Eya4), murine Six1 (pAd-shRNA-Six1) and control non-targeting adenovirus were obtained from Sirion Biotech (Martinsried, Germany). Adenovirus encoding the human p27 kip1 promoter-luciferase fragment (pAd-p27PF) was generated by subcloning the respective DNA fragment into an adenoviral plasmid.…”
Section: Adenoviral Expression Constructs and Gene Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Wayne et al [2001] have suggested that EYA4 is also important postdevelopmentally for continued function of the mature organ of Corti. Mutations that affect the EYA4 protein are known to cause non-syndromic autosomal hearing loss at the DFNA10 locus [Wayne et al, 2001;Makishima et al, 2007;Hildebrand et al, 2007].…”
Section: Discussionmentioning
confidence: 99%